The Influence of Promotion Strategies and Pricing on Consumer Purchase Decisions at Toko Grosir Sembako Jasa Niaga Marbau Labuhanbatu Utara - Hasibuan, Juni Elisa Br; Pitriyani, Pitriyani; Nasution, Meisa Fitri (Amkop Management Accounting Review (AMAR), 2026)
The purpose of this study is to examine the impact of price and promotional tactics on consumer shopping choices at the Jasa Niaga Marbau Wholesale Store in North Labuhanbatu. Researchers in this study used a quantitative strategy based on survey data. A total of 75 participants who filled out the survey were selected using a purposive sampling method, and their answers became the main source of data. Data were analyzed using SPSS version 25, which includes reliability and validity tests as well as classical assumption tests, multiple linear regression analysis, t-test, F-test, and coefficient of determination (R³). With a calculated t-value of 2.374 and a significance threshold of 0.020, the findings show that, in part, promotional methods do not have a significant impact on purchasing choices. On the other hand, purchasing choices are positively and significantly influenced by price (t-value = 7.039, p = 0.000). The F-value is determined to be 346.425 at a significance level of 0.000, indicating that both price and promotional techniques have a substantial impact on buyer choices. With an R² of 0.906, we can see that price and promotional strategies account for 90.6% of the variance in purchasing choices, while other factors account for the remaining 9.4%. Research findings show that customers at the Marbau Commercial Services Wholesale Store in North Labuhanbatu mostly look at price when making purchases, and that the store's advertising approach is ineffective.